Setting-up a European Cross-Provider Data Collection on Open Online Courses - Kalz, Marco; Kreijns, Karel; Walhout, Jaap; Castaño-Munoz, Jonatan; Espasa, Anna; Tovar, Edmundo (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
While MOOCS have emerged as a new form of open online education around the world, research is stilling lagging behind to come up with a sound theoretical basis that can cover the impact of socio-economic background variables, ICT competences, prior experiences and lifelong learning profile, variance in intentions, environmental influences, outcome expectations, learning experience and economic return on taking and completing Massive Open Online Courses (MOOCs). The potential diversity of participants of MOOCs has been taken as a starting point to develop a theoretical model and survey instrument with the goal to establish a large-scale, cross-provider data collection of participants of (European) MOOCs. This article provides and overview of the theoretical model begin the project and reflects about first experiences with the cross-provider data collection.